Investment prioritization in WP1|TARGET - Demont, Matty; Lenaerts, Bert; Paguirigan, Neale; Connor, Melanie (2024)
Since TPP design is costly and costs need to be borne by the breeding pipeline, TPPs are only required for funded market segments. TPP design for high-priority, funded market segments requires investment in collection, synthesis and outsourcing of state-of-the-art market intelligence evidence. Unfunded market segments (MS) require pipeline investment cases to either (1) convince breeders to reallocate funding from funded to unfunded MS; or (2) convince donors to fund new breeding pipelines aiming at serving unfunded MS. We propose a decision tree for the prioritization of investment in market intelligence evidence. Investment in the identification of current and future market segments (MS) has the highest priority. Current MS need to be projected to the future through economic foresight, crop, climate change and pest/disease modeling. Unserved current and future MS need to be identified. Investment in collection, synthesis and outsourcing of state-of-the-art market intelligence evidence to inform TPP design for high-priority, funded market segments has the second highest priority. Finally, investment in collection, synthesis and outsourcing of state-of-the-art market intelligence evidence to inform pipeline investment case building for high-priority, unfunded market segments has the third highest priority.